PERMASALAHAN PEMBELAJARAN DARING PADA MASA PANDEMI COVID–19 DI FKIP UNIVERSITAS WISNUWARDHANA MALANG - Zaenullah, Zaenullah; Yuniarto, Eko; Efendiy, Khoirul (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study is to (1) find out online learning during the covid-19 pandemic at the Faculty of Teacher Training and Education, Wisnuwardhana University Malang, (2) analyze the problems faced by lecturers and students in carrying out online learning during the covid-19 pandemic, (3) Analyze and identify the consequences of the problems that exist in the implementation of online learning. The design of this research method uses a qualitative descriptive method. The design of the activity is to obtain data as it is and the results emphasize meaning. The research sample was selected purposively, selected with certain considerations and objectives. This consideration is the person who is considered to know best about what the researcher expects. The research location is in the Wisnuwardhana University FKIP environment with a length of 6 months. Data collection techniques were carried out by means of participatory observation, in-depth interviews, and documentation. Meanwhile, the data analysis used the Miles and Huberman model. The results of the study show that learning is carried out in two ways, namely blended learning and hybrid learning. Many online platforms use zoom meeting, google meet, whatsapp and google forms as task assistance. Problems that are often faced are the lack of adequate networks between students, monotonous learning variations. As a result, it reduces understanding of the material, boredom in learning, limited interaction results in students becoming less active. Unequal mastery of the material.